Downregulation of hsa_circ_0004543 Activates oxLDL-Induced Vascular Endothelial Cell Proliferation and Angiogenesis - Han, Lu; Li, Dandan; Hang, Yanwen; Zong, Xiaojuan; Lv, Jiashun; Bai, Xiaolu; Lu, Yi; Zhang, Peng; Zhou, Meiling; Wu, Zhaodi; Hu, Wei (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) are novel non-coding RNAs, which show abnormal expression in several diseases, such as atherosclerosis (AS). The purpose of the present study was to reveal the association between hsa_circ_0004543 and AS. In the present study, hsa_circ_0004543 was overexpressed in human umbilical vein endothelial cells (HUVECs) induced by oxidized low-density lipoprotein (oxLDL). Inhibition of hsa_circ_0004543 expression facilitated the proliferation, migration and invasion of HUVECs, and reduced significantly their apoptotic rate following treatment with oxLDL. Furthermore, silencing of hsa_circ_0004543 activated the PI3K/AKT/NOS3 pathway in oxLDL-induced HUVECs. Collectively, these results demonstrated that hsa_circ_0004543 may play a vital role in the development of AS and affect the proliferation of HUVECs, providing a potential target for treating endothelial cell damage in AS.